2021
DOI: 10.1101/2021.01.09.21249480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The importance of non-pharmaceutical interventions during the COVID-19 vaccine rollout

Abstract: The promise of efficacious vaccines against SARS-CoV-2 is fulfilled and vaccination campaigns are starting worldwide. However, the fight against the pandemic is far from over. Here, we propose an age-structured compartmental model to study the interplay of disease transmission, vaccines rollout, and behavioural dynamics. We investigate, via in-silico simulations, individual and societal behavioural changes, possibly induced by the start of the vaccination campaigns, and manifested as a relaxation of non-pharma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 104 publications
2
22
0
Order By: Relevance
“…However, both ours and Gozzi et al [42] qualitative findings are in agreement between themselves and are consistent with the results of the earlier studies that have shown that factors that contribute to drastic increase of contact rates (such as vaccination-related behavioral change or premature reduction/removal of non-pharmaceutical interventions) may reduce the benefits of a vaccination programme [43,44,45,46].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, both ours and Gozzi et al [42] qualitative findings are in agreement between themselves and are consistent with the results of the earlier studies that have shown that factors that contribute to drastic increase of contact rates (such as vaccination-related behavioral change or premature reduction/removal of non-pharmaceutical interventions) may reduce the benefits of a vaccination programme [43,44,45,46].…”
Section: Discussionsupporting
confidence: 93%
“…In their recent work Gozzi et al [42] also have considered the impact of the feedback between the epidemic dynamics, the vaccination rollout and compliance to physical distancing on infection transmission dynamics. The authors modeled compliant behavior modifications only as pertinent to the susceptible/vaccinated population, which may have resulted in more optimistic predictions for a disease like COVID-19 whose hallmark is asymptomatic spread.…”
Section: Discussionmentioning
confidence: 99%
“…Robust evidence now shows that, under most conditions, early adoption of stringent NPIs is associated with a reduction in transmission [16][17][18][19][20][21][22][23][24][25][26][27]. However, with full vaccination still elusive, and with the possibility of vaccine-escaping variants emerging, NPIs can be expected to continue playing a significant role in managing the pandemic in the foreseeable future [28][29][30][31]. A critical question is therefore whether we can expect NPIs to continue working as the pandemic stretches into longer time frames.…”
Section: Introductionmentioning
confidence: 99%
“…While there are now several highly efficacious vaccines to prevent severe disease 12 , 13 , and possibly infection 14 , 15 , from SARS-CoV-2 (the virus that causes COVID-19), widespread vaccination will take months to years 16 , 17 and will likely need to be coupled with effective non-pharmaceutical interventions (NPIs) 18 . For countries rolling out vaccines, easing NPIs too early could jeopardize success 18 .…”
Section: Introductionmentioning
confidence: 99%